Performance Audit of Integrated Child Development Services (ICDS) in Chhattisgarh (2005-10) - CAG of India (CAG of India)
The performance review of implementation of Integrated Child Development Services (ICDS) in Chhattisgarh for the Period 2005-06 to 2009-10 revealed that all the eligible beneficiaries could not be covered under the scheme due to inadequate surveys, improper planning, non-availability of adequate project staff and lack of monitoring and supervision. Serious deficiencies were noticed in implementation of other components of the scheme such as referral services and growth monitoring. Implementation of the scheme also got affected due to poor infrastructural facilities such as non-availability of buildings for Anganwadi centres, drinking water and toilets. There were considerable delays in completion of Anganwadi centre buildings. Mani audit findings are summarised below: 1. Funds released for Supplementary Nutrition ranging between Rs 15.11 crore and Rs 132.61 crore remained unutilised due to inadequate surveys and improper assessment of eligible beneficiaries. 2. Inclusion of ineligible beneficiaries for the Supplementary Nutrition Programme resulted in avoidable expenditure of Rs 11.07 crore. 3. Issue of rice without verification of available stock and non-reconciliation of stock position led to accumulation of 2045.13 MT rice with the agencies in six test-checked projects. 4. Government of India funds amounting to Rs 5.96 crore for diarrhoea, deworming and skin diseases of children remained unutilised due to non supply of medicine kits to the Anganwadi centres. 5. Even after 35 years of implementation of the scheme, the infant mortality rate remained at 57 per 1000 live births as against the all India figure of 53. Similarly, the percentage of malnourished children stood at 51.31 as compared to the national percentage of 42.50. 6. Funds amounting to E 42.74 lakh for developing learning attitudes and values for emotional and mental preparation of children before primary education remained unutilised due to non-procurement of preschool education kits. 7. There were considerable delays, ranging from three to eight years in construction of Anganwadi Centres.
For the Period 2005-06 to 2009-10